Low and seasonal malaria transmission in the middle Senegal River basin: identification and characteristics of Anopheles vectors - Ndiath Mamadou O (Parasites & Vectors, 2012)
Abstract Background During the last decades two dams were constructed along the Senegal River. These intensified the practice of agriculture along the river valley basin. We conducted a study to assess malaria vector diversity, dynamics and malaria transmission in the area. Methods A cross-sectional entomological study was performed in September 2008 in 20 villages of the middle Senegal River valley to evaluate the variations of Anopheles density according to local environment. A longitudinal study was performed, from October 2008 to January 2010, in 5 selected villages, to study seasonal variations of malaria transmission. Results Among malaria vectors, 72.34% of specimens collected were An. arabiensis, 5.28% An. gambiae of the S molecular form, 3.26% M form, 12.90% An. pharoensis, 4.70% An. ziemanni, 1.48% An. funestus and 0.04% An. wellcomei. Anopheles density varied according to village location. It ranged from 0 to 21.4 Anopheles/room/day and was significantly correlated with the distance to the nearest ditch water but not to the river. Seasonal variations of Anopheles density and variety were observed with higher human biting rates during the rainy season (8.28 and 7.55 Anopheles bite/man/night in October 2008 and 2009 respectively). Transmission was low and limited to the rainy season (0.05 and 0.06 infected bite/man/night in October 2008 and 2009 respectively). During the rainy season, the endophagous rate was lower, the anthropophagic rate higher and L1014F kdr frequency higher. Conclusions Malaria vectors are present at low-moderate density in the middle Senegal River basin with An. arabiensis as the predominant species. Other potential vectors are An. gambiae M and S form and An. funestus. Nonetheless, malaria transmission was extremely low and seasonal.